2007
DOI: 10.1016/j.rgg.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the seismic activity of the Tuvinian and adjacent Mongolian areas with the fractal dimensionality of a fault system

Abstract: Using GIS technologies, we carried out a complex spatial analysis of the seismic activity and fractal dimensionality of fault fields in the Tuvinian and adjacent Mongolian areas. Results obtained showed that seismic activity is intrinsic to zones with the low fractal dimensionalities (1.2–1.4) of fault systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
0
1
Order By: Relevance
“…It is rather similar to the Busingol earthquake sequence, southernmost Baikal rift (Zhalkovskii et al, 1995;Delouis et al, 2002), revealing a process of long-lasting stress loading without main shock in a more than 10 years time window. Although the b-value found here ($1.5) is questionable because of the limited magnitude range (2.5-3), a high b-value ($1.3) is also found in the Busingol case (Ayunova et al, 2007). Note that the Busingol crisis ended by a M w 6.3 event in December 1991 (Bayasgalan et al, 2005).…”
Section: Triggering Mechanisms Of Sequences and Comparison To Other Scontrasting
confidence: 58%
“…It is rather similar to the Busingol earthquake sequence, southernmost Baikal rift (Zhalkovskii et al, 1995;Delouis et al, 2002), revealing a process of long-lasting stress loading without main shock in a more than 10 years time window. Although the b-value found here ($1.5) is questionable because of the limited magnitude range (2.5-3), a high b-value ($1.3) is also found in the Busingol case (Ayunova et al, 2007). Note that the Busingol crisis ended by a M w 6.3 event in December 1991 (Bayasgalan et al, 2005).…”
Section: Triggering Mechanisms Of Sequences and Comparison To Other Scontrasting
confidence: 58%
“…However, various studies have demonstrated that fault geometric shape and spatial distribution exhibit pronounced fractal structural characteristics. Fractal parameters can quantitatively depict the complexity of fault systems [35][36][37][38].…”
Section: Fractal Analysismentioning
confidence: 99%